Alethia: Precatio e primo libro. Introduzione, testo latino, traduzione e commento. : Alethia: Precatio and first book. Introduction, Latin text, translation and commentary - Isabella D'Auria; Claudio Mario Vittorio (FedOA - Federico II University Press, 2014)
In the context of Christian paraphrastic poetry, the Claudio Mario Vittorio$1 (Bs Alethia is a significant example of the synthesis between the classical and the Christian world during the Late antiquity. The work, probably composed in the first half of the 5th century, is a hexametric rewrite in three books, preceded by a Precatio, of the first 19 chapters of Genesis book, from the creation of the world to the destruction of Sodom and Gomorrah. This essay offers to the reader the translation and commentary of the Precatio and the first book of the poem. It aims to highlight the complex cultural plot of the text and, at the same time, analysing, with a predominantly intertextual approach, the paraphrasing procedures adopted by Claudio Mario Vittorio in the verse of biblical narrative. Moreover, the volume aims to give a proper account of a paraphrastic poem that deals in an admirable manner sacred history, biblical exegesis and tradition.s
Italian
Keywords: xxxx; Claudio Mario Vittorio; Christian Poetry; Ancient Christian Literature